The Role of Social Media Influencers in the Cryptocurrency Market Performance Movement - Ronniko Agus Frinico (Universitas Darussalam Gontor, 2023)
During this pandemic, there are many people who just stay at home, so they think about investing in order to get additional income, one of which is investing in crypto, until finally, crypto investment becomes a trend for people in Indonesia. The pump and dump pattern known in the cryptocurrency market shows that a high market capitalization makes a project in cryptocurrency healthy and not vulnerable to market manipulation. Many factors influence the increase or decrease in the price of cryptocurrencies, although this digital currency is known to be resilient to government intervention, there are many other factors that contribute to its price volatility. One of them is famous influencers such as Elon Musk, Michael Saylor, Changpeng Zhao, and many more. These influencers often tweet on social media such as Twitter, with a single positive or negative tweet that can increase or decrease the price of cryptocurrencies such as BTC and alternative cryptocurrencies.